Decision Support System dalam Menentukan Mahasiswa Bermasalah Menggunakan Metode Topsis - Adinda Dhea Pramitha; Anis Fatul Fu'adah; Agung Teguh Wibowo Almais; Laela Nurul Qomariyah (Jurnal Ilmiah Informatika, 2020)
At present many old semester students are starting to be undisciplined in attending lectures, this is due to the increasing burden of their assignments causing the enthusiasm of students to relax. This can create serious problems in the department because it can affect the accreditation level of the department. The purpose of this journal, which is to help the department admins to determine students who have problems in the field of lectures, so that the department can find out how many problem students can affect the accreditation of majors. In this journal, we implement the Decision Support System for manufacturing the system. With the TOPSIS method for calculations on the system, and using the Confusion Matrix for testing the system. From testing using confusion matrix, it can be concluded that precision produces 75%, recall produces 75%, accuracy produces 73%, and f-measure produces 75%. This shows that the system has a pretty good ability because it has exceeded the value of 70%.